Dithienylethene‐Based Photochromic Siloles: A Straightforward and Divergent Synthetic Strategy. Issue 22 (21st April 2021) - Devillard, Marc; Nour Eddine, Nour; Cordier, Marie; Alcaraz, Gilles
Abstract: A straightforward synthetic methodology for the preparation of photochromic siloles based on the dithienylethene motif is developed. It relies upon an efficient palladium‐catalyzed annulation reaction of a 2, 3‐bis(3‐thienyl)‐silirene with terminal alkynes in mild conditions. The reaction is functional group‐tolerant and can be performed in high yields with a variety of functional terminal alkynes. It can even be extended to a polymeric polypropargylmethacrylamide (PPMA) substrate affording the corresponding photochromic polymer with different degree of photochromic unit incorporation by simply adjusting the polymer/ silirene stoichiometric ratio. Abstract : A straightforward preparation of photochromic siloles based on the dithienylethene motif is developed. It relies upon an efficient palladium‐catalyzed annulation reaction of a 2, 3‐bis(3‐thienyl)‐silirene with terminal alkynes in mild conditions. The reaction is functional group‐tolerant and can be performed in high yields with a variety of functional terminal alkynes.